INTERPRETATIVE ISSUES IN CHURCH CHORAL MUSIC - MURARU, Aurel (Studia Universitatis Babes-Bolyai Musica, 2016)
The present endeavour aims primarily at emphasizing the issues related to the interpretation of Orthodox liturgical choral music. Although, at first glance, the music of the Divine Liturgy seems to be just another art of sound, in reality it goes far beyond the limits of a “simple” work of art. The religious sermon can in no way be compared to a concert, with performers and listeners. The parishioners are not merely an audience from a concert hall, but, together with the priests performing the ceremony, they participate organically and actually to the development of the religious sermon. Hence, it is important to become aware of the fact that, in the Christian cult, the chanting is not merely decorative, but it accompanies and continually deepens the important moments of the divine service.